Monopile foundations under complex cyclic lateral loading - Richards, I; Richards, I (2019)
The vast majority of offshore wind turbines are supported on monopile foundations. These foundations experience lateral loading which is both cyclic and complex: continuously varying in amplitude, direction, frequency and eccentricity with the environmental and turbine operation conditions. The effect of cyclic loading on the accumulated rotation (ratcheting), strength and stiffness of the foundation must be considered, while advanced structural dynamic modelling requires prediction of the cyclic hysteretic response. However, there are currently no commonly accepted design methods for predicting the cyclic response of monopile foundations, particularly under the complex loading to which they are exposed.